2017
DOI: 10.1152/ajpgi.00344.2016
|View full text |Cite
|
Sign up to set email alerts
|

Protective roles of hepatic GABA signaling in acute liver injury of rats

Abstract: γ-Aminobutyric acid (GABA) is produced by various cells through the catalytic activity of glutamic acid decarboxylase (GAD). Activation of type-A GABA receptor (GABAR) inhibits stem cell proliferation but protects differentiated cells from injures. The present study investigated hepatic GABA signaling system and the role of this system in liver physiology and pathophysiology. RT-PCR and immunoblot assays identified GAD and GABAR subunits in rat livers and in HepG2 and Clone 9 hepatocytes. Patch-clamp recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 47 publications
4
26
3
Order By: Relevance
“…Neurotransmitter GABA has been widely studied in human patients as treatment for neuronal diseases including Alzheimer's disease [18]. In addition, several studies have shown that GABA plays an important role in non-neuronal tissues and that it can be used to treat diseases including liver injury [19]. In kidney, GABA is shown to have anti-inflammatory properties and promote fibroblast proliferation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmitter GABA has been widely studied in human patients as treatment for neuronal diseases including Alzheimer's disease [18]. In addition, several studies have shown that GABA plays an important role in non-neuronal tissues and that it can be used to treat diseases including liver injury [19]. In kidney, GABA is shown to have anti-inflammatory properties and promote fibroblast proliferation [20].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table , from the first to the third day, mice in the GABA + ethanol, muscimol + ethanol and bicuculline + ethanol groups were i.p. injected daily with GABA (1.5 mg kg −1 body weight daily; Sigma‐Aldrich, St. Louis, MO, USA) (Xiang et al, ), muscimol (GABA A R agonist, 1.2 mg kg −1 body weight daily; Sigma‐Aldrich) (Wang et al, ; Xiang et al, ) and bicuculline (GABA A R antagonist, 2.0 mg kg −1 body weight daily; Sigma‐Aldrich) (Soltani et al, ; Wang et al, ), respectively. Mice in the control and ethanol groups were i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Early studies have revealed that both rat and human hepatocytes contain high concentrations of GABA (Minuk, ) and express GABA A R subunits (Minuk et al, ).Recently, we demonstrated that GABA A R‐mediated auto‐ and paracrine signaling mechanisms exist in different types of cells in the liver. Moreover, the hepatic toxin d ‐galactosamine alters the expression of GABA A R in hepatocytes and activation of hepatic GABA signaling protects rat liver function from d ‐galactosamine injury (Wang et al, ). Other studies have shown that acute ingestion of ethanol raises plasma GABA levels in humans (Bannister, Levy, Bolton, & Losowsky, ) and that GABA protects hepatocytes from ethanol cytotoxicity in vitro through unknown mechanism(s) (Norikura, Kojima‐Yuasa, Suzuura, & Matsui‐Yuasa, ).…”
Section: Introductionmentioning
confidence: 99%
“…15 Nonetheless, the mechanisms require further investigation. 18 Outside the CNS, many studies have discovered new functions of this system in peripheral organs such as the pancreatic islet, 19 liver 20,21 and human fallopian tube, 22 as well as in the cardiovascular system. 16 Moreover, GABA A and GABA B receptors participate in cardiac function modulation by tonic sympathetic outflow in the paraventricular nucleus of the hypothalamus 17 ; exogenous GABA in the CNS also mediates autonomic nerve activity to decrease coronary vessel resistance and exert an anti-arrhythmic effect on ischemic heart tissue.…”
Section: Introductionmentioning
confidence: 99%
“…16 Moreover, GABA A and GABA B receptors participate in cardiac function modulation by tonic sympathetic outflow in the paraventricular nucleus of the hypothalamus 17 ; exogenous GABA in the CNS also mediates autonomic nerve activity to decrease coronary vessel resistance and exert an anti-arrhythmic effect on ischemic heart tissue. 18 Outside the CNS, many studies have discovered new functions of this system in peripheral organs such as the pancreatic islet, 19 liver 20,21 and human fallopian tube, 22 as well as in the cardiovascular system. Injection of exogenous GABA via the caudal vein significantly decreases the incidence of arrhythmias induced by aconitine, 23 indicating a potential peripheral therapeutic effect of the GABAergic signalling system in the treatment of cardiovascular diseases such as heart failure, MI and arrhythmias.…”
Section: Introductionmentioning
confidence: 99%